Vector-Borne Disease Risk Assessment Among Households: A Cross-Sectional Epidemiological Investigation - Anu Joseph; Pinky Jose; Ajeena Joseph; Jincy Mathew (International Journal of Evidence Based Nursing And Practices, 2026)
The study was conducted to assess the risk of vector-borne diseases among households of the selected ward of Athirampuzha Panchayath, Kottayam. Objectives of the study were to assess the percentage of houses infested with larvae or pupae of mosquito (house index (HI): total number of positive houses/total houses × 100), to identify the percentage of water holding containers infested with larvae or pupae of mosquito (container index (CI): total number of positive containers/total containers × 100) and to determine the number of positive containers per houses inspected (Breteau index (BI): number of positive containers/total houses × 100) among households in the study area. A survey design using a convenience sampling technique was used to select 72 households. The tool for data collection was a self-designed observational checklist. The result showed that among the households surveyed, 11 (15.3%) were infested with larvae or pupae of mosquitoes, HI ≥ 5%: high risk of vector-borne diseases. Among the water holding containers inspected, 10 (28.6%) containers were infested with larvae or pupae of mosquitoes. CI ≥ 10%: high risk of vector-borne diseases. Among the households inspected, 10 (13.9%) water holding containers were infested with larvae or pupae of mosquitoes per house inspected, BI 5-19%: moderate risk of vector-borne diseases.
Keywords: Risk assessment; household pupae of mosquito; moderate risk; vector-borne diseases